Affective judgments, environmental determinants, and physical activity in emerging and young adults. - Turrisi, Taylor B.; Lagoa, Constantino M.; Conroy, David E. (Psychology & Health, 2024)
Affective judgements represent a promising target for promoting physical activity among adults. This study examined whether relations between affective judgments and physical activity are robust after adjusting for social, built, and natural environmental determinants. Prospective cross-sectional study with 173 adults (70.1% female) aged 18–29 years who self-reported less than 90 minutes of moderate-to-vigorous physical activity. Physical activity volume (total daily step count, total activity counts) and durations of intensity-specific physical activity (light-intensity activity and moderate-to-vigorous intensity) were assessed for a seven-day period via waist-worn ActiGraph wGT3X-BT accelerometer. Affective judgements were not statistically associated with measures of physical activity volume or intensity-specific physical activity after adjusting for environmental influences. Support for exercise from friends was positively associated with measures of physical activity volume and moderate-to-vigorous physical activity duration. More favorable perceptions of the built environment were positively associated with moderate-to-vigorous intensity physical activity and negatively associated with duration of light-intensity physical activity. Longer photoperiods were associated with more light-intensity physical activity. Physical activity interventions for young and emerging adults reporting inactivity should target environmental determinants first and possibly wait until participants have a motivational stake in physical activity before targeting affective judgments.